2019
DOI: 10.1017/s0266462319000187
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Health System Values in Health Technology Assessment: The Use of Evidence-Informed Deliberative Processes

Abstract: Health technology assessment (HTA) is increasingly used around the globe to inform resource allocation decisions. Furthermore, the importance of using explicit and transparent criteria for coverage decision making in line with health system values has been acknowledged. However, the values of a health system are often not explicitly taken into account in the HTA process. This situation influences the allocation of scarce resources and could lead to a discord between the HTA outcome and the values of the health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…We could not identify from the sources studied how the decision criteria are selected including whether stakeholders are involved in the selection ( Supplementary file 1 : Table S2). Previous research on linking health system values and decision criteria also found that it is difficult to retrieve this information from written sources 35 For learning purposes it would be valuable to study the selection processes of decision criteria as used by HTA bodies in more detail using for example semi-structured interviews.…”
Section: Introductionmentioning
confidence: 99%
“…We could not identify from the sources studied how the decision criteria are selected including whether stakeholders are involved in the selection ( Supplementary file 1 : Table S2). Previous research on linking health system values and decision criteria also found that it is difficult to retrieve this information from written sources 35 For learning purposes it would be valuable to study the selection processes of decision criteria as used by HTA bodies in more detail using for example semi-structured interviews.…”
Section: Introductionmentioning
confidence: 99%
“…The biggest thematic cluster considers the assessment and selection of healthcare and health technologies, within which a subarea of medical and biomedical technology selections was distinguished. Health Technology Assessment (HTA) is a wellestablished research field (Oortwijn & Klein, 2019). Within the search results, documents related to healthcare technologies or health constitute almost 30 % in WoS and around 14 % in Scopus.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Given the increasing interest and focusin this journal and beyondon both deliberation in MCDA (26)(27)(28) and how deliberation can and should be used to inform HTA more generally (29), this commentary provides further insights and arguments to guide ongoing experimentation and evaluation of different deliberative approaches for health priority-setting on the bases of quality, transparency, and other important goals of decision making. To this end, we propose that it may be more constructive to move away from a typology that distinguishes MCDA in terms of quantitative and qualitative assessment and instead focus on how well different deliberative, multi-criteria approaches are able to incorporate and balance the various types of qualitative and quantitative informational inputs that are morally relevant to the decisions at hand.…”
Section: Resultsmentioning
confidence: 99%